Quantitative imaging of endosome acidification and single retrovirus fusion with distinct pools of early endosomes. - Padilla-Parra, S; Matos, P; Kondo, N; Marin, M; Santos, N; Melikyan, G (2012)
Diverse enveloped viruses enter host cells through endocytosis and fuse with endosomal membranes upon encountering acidic pH. Currently, the pH dynamics in virus-carrying endosomes and the relationship between acidification and viral fusion are poorly characterized. Here, we examined the entry of avian retrovirus that requires two sequential stimuli--binding to a cognate receptor and low pH--to undergo fusion. A genetically encoded sensor incorporated into the viral membrane was used to measure the pH in virus-carrying endosomes. Acid-induced virus fusion was visualized as the release of a fluorescent viral content marker into the cytosol. The pH values in early acidic endosomes transporting the virus ranged from 5.6 to 6.5 but were relatively stable over time for a given vesicle. Analysis of viral motility and luminal pH showed that cells expressing the transmembrane isoform of the receptor (TVA950) preferentially sorted the virus into slowly trafficking, less acidic endosomes. In contrast, viruses internalized by cells expressing the GPI-anchored isoform (TVA800) were uniformly distributed between stationary and mobile compartments. We found that the lag times between acidification and fusion were significantly shorter and fusion pores were larger in dynamic endosomes than in more stationary compartments. Despite the same average pH within mobile compartments of cells expressing alternative receptor isoforms, TVA950 supported faster fusion than TVA800 receptor. Collectively, our results suggest that fusion steps downstream of the low-pH trigger are modulated by properties of intracellular compartments harboring the virus.